The Influence of Task Based Language Teaching and Learning Motivation Toward Writing Achievement - Arief Rahman Hakim (UNMUH BABEL PRESS, 2020)
This study was to investigate the influence of task based language teaching and learning motivation toward writing achievement. The population of this study was the eleventh grade students at SMK N 3 Palembang. The sample was 64 students taken by using cluster random sampling. In carrying out of the research, the writer used an experimental method; factorial design. The writer distributed pretest, posttest, and attitude questionnaire in collecting the data. Then, in analyzing the data the writer used t-test and two-way ANOVA. The result of this study analysis indicated that: (1) there was a significant difference in writing achievement between the student who taught by using TBLT and those are taught using conventional technique, (2) there was significant difference in writing achievement between the students who have high motivation by using TBLT and conventional teaching technique, (3) there was significant difference in writing achievement between the students who have low motivation by using TBLT and conventional teaching technique, (4) there was significant difference in writing achievement between the students who have low and high motivation by using TBLT, and (5) there was an interaction effect of technique used and student’s motivation in improving writing achievement.